In Search of Emerging Same-Sex Sexuality: Romantic Attractions at Age 13 Years. - Li, Gu; Hines, Melissa (Archives of Sexual Behavior, 2016)
Sex-typed behavior in childhood is significantly related to sexual orientation in adulthood. In addition, same-sex attractions in early adolescence are more non-exclusive than in adulthood and can differ from later same-sex orientations. However, little research has focused on romantic attractions as they emerge during early adolescence. Drawing a sample from the Avon Longitudinal Study of Parents and Children (197 girls, 204 boys), the current study examined whether same-sex romantic attractions at age 13 years were exclusive, and whether they were predicted by sex-typed behavior at age 3.5 years. No young adolescents in this sample reported exclusive same-sex attractions, and increased same-sex attractions were not significantly related to reduced other-sex sexualities. Childhood sex-typed behavior did not significantly predict early same-sex attractions, suggesting that early same-sex attractions differ from later same-sex orientations. The current study highlights the importance of studying the development of sexuality beginning prior to adulthood.